RECONSTRUCTION OF COMPLEX BUILDING AS A METHOD OF SUSTAINABLE DEVELOPMENT OF RESIDENTIAL ENVIRONMENT - and and (Municipal economy of cities (Technical science), 2013)
Highlight some aspects of the development of methodological foundations of an effective comprehensive reconstruction in the context of theories of urban development. Rehabilitation of housing is seen as a process that reflects the essence of the new economic relations.